2013
DOI: 10.1111/j.1477-2574.2012.00549.x
|View full text |Cite
|
Sign up to set email alerts
|

Results of pancreatic surgery in the elderly: is age a barrier?

Abstract: Results from this study suggest that while elderly patients can safely undergo a pancreatic resection and that age alone should not preclude a pancreatic resection, there is still significant morbidity and mortality in the octogenarian subgroup with poor long-term survival with the need for quality-of-life assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
37
3
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 21 publications
3
37
3
4
Order By: Relevance
“…Our findings are in accordance with the recent Dutch guideline on pancreatic cancer [17], stating that high age alone should not be a contraindication for pancreatic surgery. The proportion of octogenarians in our study (4.7%), however, was in the lower range compared to reports from specialised centres (4.5-17%) [5][6][7][8] and compared to population-based studies on this subject reporting 5.7-12.4% octogenarians [3,4,10]. Despite increasing resection rates in the course of our study, 30-day postoperative mortality slightly decreased in elderly patients who underwent resection for pancreatic or periampulary carcinoma.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…Our findings are in accordance with the recent Dutch guideline on pancreatic cancer [17], stating that high age alone should not be a contraindication for pancreatic surgery. The proportion of octogenarians in our study (4.7%), however, was in the lower range compared to reports from specialised centres (4.5-17%) [5][6][7][8] and compared to population-based studies on this subject reporting 5.7-12.4% octogenarians [3,4,10]. Despite increasing resection rates in the course of our study, 30-day postoperative mortality slightly decreased in elderly patients who underwent resection for pancreatic or periampulary carcinoma.…”
Section: Discussioncontrasting
confidence: 55%
“…Furthermore, no information was available on postoperative complications and cause of death. Overall, mixed results were found on the association of high age and morbidity after pancreatic surgery for cancer [2,5,8,12]. However, in studies that differentiated between surgical and non-surgical complications, age differences were particularly found in non-surgical complications [12,25].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Elderly patients will likely have more pre-operative comorbidities affecting peri-operative morbidity and mortality, and surgeons will be required to determine which elderly patients will be reasonable surgical candidates. Previous studies have shown varied clinical outcomes of elderly patients undergoing PD (7)(8)(9)(10)(11)(12)(13)(14). While there are studies that suggest advanced age to be a risk factor associated with increased postoperative complications and mortality after PD (7,8), others have shown no increased risk with advanced age (9)(10)(11)(12)14).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, few authors have evaluated the short-and long-term outcomes of pancreatic resection for pancreatic adenocarcinoma in patients aged 75 years and older. [8][9][10][11] Therefore, the short-term outcomes and long-term survival of pancreatic resection for pancreatic adenocarcinoma in elderly patients are still unclear. In addition, generally, elderly patients often have comorbidities and age-related physiologic problems that can lead to greater postoperative complications or poor survival than in nonelderly patients.…”
mentioning
confidence: 99%